KARAKTERISTIK TANAH TIMBUN SEBAGAI PENGGANTI SUBGRADE DI LAHAN GAMBUT - Srihandayani, Susy; Mazni, Deni Irda (Universitas Muhammadiyah Palembang, 2021)
Soil is the most important material as the base in construction. Soil is also used as landfill material on peatlands in the field of Civil Engineering work such as the subgrade, backfill, and dams. Landfill soil as a substitute for subgrade on peatlands (such as in Dumai city) has characteristics that are following existing regulations. The characteristics of peat soil are low bearing capacity, high compressibility, very high water content, and high void ratio. Therefore it is necessary to improve the land in peat soil areas. One of the improvements is to replace it with soil that has adequate carrying capacity potential. For the city of Dumai city, the materials were taken in 3 Quarry areas, namely Ex. Balai Raja Duri, Ex. Bukit Kapur dan Ex. Ujung Tanjung. It is necessary to investigate the landfill soil such as its physical and mechanical properties which are tested in the soil mechanics laboratory. In laboratory testing, soil samples are taken to a depth of approximately 50 cm from the soil surface (for undisturbed samples). Among the results of the laboratory tests, the water content values (17.85%, 21.4%, and 20%); void ratio (1.03; 1.46; and 1.63); plasticity index (13.96; 8.09; 9.6), respectively for Quarry Ex. Balai Raja Duri, Ex. Bukit Kapur dan Ex. Ujung Tanjung and CL soil classification for the 3 Quarry. So it can be concluded that the 3 Quarry is suitable to be used as a substitute for subgrade on peatlands.Keywords: Soils, Subgrade, bearing capacity